ESRA19-0706 Ultrasound perioperative management of block sterility and aseptic technique minimum standards. (30th August 2019) - Provenzano, D
Abstract : Introduction: Ultrasound imaging is a useful diagnostic and interventional device in a variety of settings. In both regional anesthesia and chronic pain medicine, the use of ultrasound to guide interventional procedures and also for diagnostic purposes continues to grow. When performing ultrasound-guided interventional procedures for acute and chronic pain, it is important to limit the risk of infection. In this lecture, we will discuss the perioperative management of ultrasound block sterility and appropriate aseptic standards to limit infection. the two main vectors of infection for ultrasound guided procedures include ultrasound equipment and gel. Ultrasound equipment: Ultrasound equipment can be a source of nosocomial infections in patients undergoing interventional procedures. 1 When uncovered, ultrasound equipment can come into direct contact with the patient. Multiple studies have demonstrated the risk of contamination and the risk of cross infection through ultrasound equipment. a study examining 100 consecutive patients undergoing routine abdominal/pelvic ultrasound scans demonstrated that, in 13% of the procedures, the probes were found to be colonized with Staphylococcus aureus. 2 In addition, in 7%, the contaminating strain was the same bacteriophage type as that isolated from the patient either before or after the examination (i.e. interpatient transfer). In individuals that were colonized with Staphylococcus aureus prior to the ultrasound examination, 21% of the probes became colonized with the same phage type following scanning. In another study examining 44 transducer heads, 27% of the transducer heads were contaminated. 3 Fowler et al. 4 in a prospective study in 40 patients demonstrated that, on average, 128 colony forming units (CFUs) were transferred by unclean probes. In addition, when a patient was known to have MRSA the transmission rate of MRSA was 41%. When utilizing ultrasound equipment, it is important that institutional and national standards are followed for the cleaning and disinfection of ultrasound equipment. Ultrasound gel: Multiple case reports have also been published identifying ultrasound gel as a source of nosocomial infection. In these case reports, both manufacturer and user processes have been identified as sources of contamination for various bacterial organisms, including Klebsiella pneumoniae 5, Burkholderia cepacia 6–9, Achromobacter xylosoxidans 10, and Staphylococcus aureus 11 . Intrinsically contaminated ultrasound gel, at the time of manufacturing, has been responsible for multiple cases of nosocomial infection. Hutchinson et al. 6 identified serious Burkholderia cepacia infections at tertiary care centers that resulted from contaminated ultrasound gel that originated directly from the manufacturer. 6 Respiratory infections from Pseudomonas aeruginosa occurred in patients that had undergone cardiovascular surgery where intraoperative TEE was utilized. 12 After an infection control investigation with the assistance of molecular typing, ultrasound gel multidose bottles were identified as the source of the Pseudomonas aeruginosa . Furthermore, sealed, unopened bottles also contained the same isolate of Pseudomonas aeruginosa, suggesting that contamination occurred at the time of manufacturing. Besides contamination at the time of manufacturing, contamination of ultrasound gel in the spread of infection may also occur from inappropriate use of products. An outbreak of Achromobacter xylosoxidans associated with ultrasound gel used for transrectal ultrasound-guided prostate biopsies occurred from contaminated ultrasound gel through which biopsy needles passed. 10 the ultrasound gel originated from a large supply bag that was used to refill ultrasound gel containers. In addition, nosocomial outbreaks of Klebsiella pneumoniae in six adult women and two neonates, and Burkholderia cepacia in a pediatric institution, have occurred secondary to inappropriate user processes for handling ultrasound gel. 5 Efforts to reduce gel-borne contamination have occurred through both the publishing of clinical recommendations by international and national communities and the modification of the manufacturing process. In response to this health concern, multiple medical associations and government agencies have published warnings and proposed preliminary clinical recommendations to minimize infection when using sterile and nonsterile medical gels. In 2004, following several cases of bacteremia and septicemia that occurred from the utilization of contaminated ultrasound gel, Health Canada published practice recommendations for the use of both sterile and nonsterile gels. 13 These recommendations have been endorsed by many professional associations, including the Canadian Society of Diagnostic Medical Sonographers, the Society of Diagnostic Medical Sonography, and the American Institute of Ultrasound in Medicine. In April 2013, the Australian Sonographers Association published a background paper on the safe use and storage of ultrasound gel to prevent nosocomial infections, including cross infections. 14 the stimulus for this background paper originated from the safety alerts and recalls released in 2012 by the Australian Department of Health Therapeutic Goods Administration due to the confirmed presence of bacterial contamination in ultrasound gel. In the United States, recommendations based on expert opinion have been proposed to minimize clinical risk. 15 These recommendations build on the Health Canada recommendations that suggested the use of single-use sterile gels for invasive procedures involving: neonates, all procedures involving sterile equipment or non-intact skin, and for procedures on intact mucous membranes. the additional recommendations proposed by Oleszkowicz et al. 15 are shown in table 1 . In addition, a 'call' was made for the development of standardized professional society guidelines on the appropriate use of ultrasound transmission gel that could be adopted by healthcare practitioners and facilities. Numerous factors can contribute to the risk of contaminating ultrasound gel and thus increase the spread of infection. For example, when using nonsterile ultrasound gel, multiple inappropriate practices may increase the risk of infection, including: 1) failing to wipe the outside of the bottle with a disinfectant between patients, 2) not following the expiration date of a bulk refilling container, 3) placing the tip or dispensing nozzle of the ultrasound gel bottle in direct contact with a patient, environment, or instrumentation, 3) reusing the ultrasound gel bottle after scanning individuals with known contact precautions, 4) refilling an ultrasound gel bottle by inserting the tip of the refillable bottle into the bulk container to aspirate contents, and 5) utilizing inappropriate gel warming methods. In addition, it has been recommended that, if refillable containers are used, they should not be topped off, and prior to refilling the container, should be washed in hot soapy water or hospital-grade disinfectant. 13 The healthcare community often assumes that, when non-invasive diagnostic ultrasound scans are performed on patients with intact skin, ultrasound gel is a noncritical item and sterility is not essential. 15 16 However, significant infections have occurred even in these situations. Weist et. al. 11 reported methicillin-susceptible Staphylococcus aureus infections in neonates undergoing non-invasive hip ultrasound examinations that were associated with contaminated dispensing spatula and gel bottles. Besides the clinical recommendations made by multiple societies, ultrasound gel manufacturers have also attempted to limit gel-borne contamination through the addition of stabilizing bacteriostatic preservatives such as parabens. 6 First introduced in the 1930s, parabens (alkyl esters of p -hydroxybenzoic acid) are a type of preservative used in cosmetic, pharmaceutical, and industrial products that were thought to have significant bacteriostatic (stop the growth or multiplication of bacteria) rather than bactericidal (destroy bacteria) effects. Examples of parabens include methylparaben, ethylparaben, propylparaben, and butylparaben. Although parabens are thought to have a broad spectrum of inhibiting activity against yeast, fungi, and bacteria, multiple reports have demonstrated resistance to these agents and ultimately questioned their bacteriostatic effects. 1 6, 17–21 In 1995, Muradali et al. 1 demonstrated that ultrasound gel containing parabens did not effectively limit the growth of Staphylococcus aureus. a recent study suggests that ultrasound gel containing parabens is only marginally effective at inhibiting the growth of specific bacterial species on a growth promoting substrate. 20 In this study, the ultrasound gel containing parabens was more effective at inhibiting the growth of gram-positive bacteria (specifically Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus) than gram-negative bacteria (specifically Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa) . the bacteriostatic effects of ultrasound gel containing parabens did not inhibit the growth of Pseudomonas aeruginosa and only limited the growth of Escherichia coli and Klebsiella pneumoniae for 24 hours. Gram-negative bacteria have been shown to have the ability to degrade, hydrolyze, and develop resistance to parabens. 6 21 22 Conclusion: In conclusion, based on the information provided, it is clear that both ultrasound gel and equipment both serve as vectors for infection. Multi-society guidelines have provided recommendations for aseptic technique for ultrasound guided interventional pain procedures. 23 These recommendations will be discussed. When the appropriate steps are taken the risk of infection is low. 24 References: AJR American journal of roentgenology 1995;164(6):1521–1524. Journal of ultrasound in medicine: official journal of the American Institute of Ultrasound in Medicine 1989;8(11):619–620. Physiotherapy Research International: the Journal for Researchers and Clinicians in Physical Therapy 2006;11(2):61–71. Radiology 1999;213(1):299–300. Journal of Clinical Microbiology 1998;36(5):1357–1360. Infection control and hospital epidemiology: the official journal of the Society of Hospital Epidemiologists of America 2004;25(4):291–296. Infection control and hospital epidemiology: the official journal of the Society of Hospital Epidemiologists of America 2006;27(4):362–366. The Journal of Hospital Infection 2010;76(4):360–361. The Journal of Urology 1993;149(3):523–526. The Journal of Urology 2011;185(1):144–147. Infection Control and Hospital Epidemiology: the Official Journal of the Society of Hospital Epidemiologists of America 2000;21(12):761–764. CDC MMRR 2012;61:262–264. CMAJ: Canadian Medical Association journal = journal de l'Association medicale canadienne 2004;171(11):1348. Surgical neurology 2002;58(1):5–11; discussion 11–12. Infection control and hospital epidemiology: the official journal of the Society of Hospital Epidemiologists of America 2012;33(12):1235–1237. Journal of Diagnostic Medical Sonography 2010;26(4):190–197. Die Pharmazie 1988;43(10):701–703. Dermatitis: Contact, Atopic, Occupational, Drug: Official Journal of the American Contact Dermatitis Society, North American Contact Dermatitis Group 2005;16(2):57–66; quiz 55–56. Clinical Radiology 1988;39(3):245–246. Reg Anesth Pain Med 2013;38(5):415–424. Applied and Environmental Microbiology 2001;67(6):2404–2409. Journal of Applied Microbiology 1997;83(3):322–326. Regional Anesthesia and Pain Medicine 2012;37(6):657–664. Reg Anesth Pain Med 2015;40(1):82–84.